The virtuous citizen : patriotism in a multicultural society - Soutphommasane, Tim (Cambridge University Press, 2012)
"What does it mean to be a citizen in a multicultural society? And what role must patriotism play in defining our relationship with our country and fellow citizens? In The Virtuous Citizen Tim Soutphommasane answers these questions with a critical defence of liberal nationalism. Considering a range of contemporary political debates from Europe, North America and Australia, over issues including multiculturalism, national history, civic education and immigration, Soutphommasane argues that a love of country should be valued alongside tolerance, mutual respect and public reasonableness as a civic virtue. A liberal form of patriotism, grounded in national identity, is if anything essential to a successful polity in a diverse society. This book is required reading not only for political theorists and philosophers but also researchers and professionals in political science, sociology, history and public policy"--